2008
DOI: 10.2215/cjn.02810707
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Treatment with Sevelamer Increases Serum Fetuin-A Concentration and Improves Endothelial Dysfunction in Chronic Kidney Disease Stage 4 Patients

Abstract: Background and objectives: Vascular calcification and endothelial dysfunction contribute to the development of cardiovascular disease in patients with chronic kidney disease (CKD). Sevelamer, a non-calcium-based phosphate binder, has been shown to attenuate cardiovascular calcification in CKD patients, although the exact mechanism has not been clarified. This study was designed to investigate the effect of short-term sevelamer treatment on both serum fetuin-A concentrations and endothelial dysfunction seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 41 publications
1
85
1
8
Order By: Relevance
“…Caglar et al studied 50 nondiabetic, hyperphosphatemic patients at CKD stage 4 and observed that an 8-week course of treatment with sevelamer was associated with less inflammation, higher fetuin-A levels and better endothelial function, compared with calcium acetate. 25 Yilmaz et al for their part recently reported, in a similar cohort, a modulation of FGF23 levels by phosphate binders, independently associated with improvement of endothelial function. 26 …”
Section: Epidemiological and Interventional Studiesmentioning
confidence: 86%
“…Caglar et al studied 50 nondiabetic, hyperphosphatemic patients at CKD stage 4 and observed that an 8-week course of treatment with sevelamer was associated with less inflammation, higher fetuin-A levels and better endothelial function, compared with calcium acetate. 25 Yilmaz et al for their part recently reported, in a similar cohort, a modulation of FGF23 levels by phosphate binders, independently associated with improvement of endothelial function. 26 …”
Section: Epidemiological and Interventional Studiesmentioning
confidence: 86%
“…We demonstrated its beneficial effect for arterial stiffness parameters in dialysis patients previously [124] . A recent study in nondiabetic CKD patients demonstrated a significant increase in fetuin-A after treatment with sevelamer [125] . According to these results, sevelamer may attenuate the progression of arterial pathology in CKD, at least partly through the elevation of fetuin-A.…”
Section: Future Directions -New Therapeu-tic Pathwaysmentioning
confidence: 94%
“…5/6 nephrectomy was performed under general anesthesia with ligation of one of the extrarenal branches of left renal artery and right nephrectomy. 7 The special food containing high phosphate (P) and high P+ sevelamer were manufactured in MBD Yem Ticaret in Gebze-Kocaeli. Eighteen rats were included in the study and were divided into three groups.…”
Section: Methodsmentioning
confidence: 99%
“…6 Endothelial dysfunction was shown to be a risk factor in apparently healthy patients for the development of atherosclerosis years before atheromatosis plaques were formed. 7 Furthermore, administration of the sevelamer to maintenance hemodialyis patients is associated with a significant decrease in hs-CRP, IL-6 and serum endotoxin levels. On the other hand, increased translocation of endotoxin to the systemic circulation was shown to be correlated with inflammation in various animal models.…”
Section: 4mentioning
confidence: 99%